Analysis of the environmental characteristics and impacts of agricultural production in the Western Department of the Republic of Haiti - Charles, Ralph; Célia de Oliveira, Regina; Almussa Leite Torres, Guilherme; Greco, Roberto (Geografares, 2023)
In the Republic of Haiti, agriculture is one of the main economic sectors. In the Western Department, more than half of the population lives in rural areas and relies on agriculture as their primary source of livelihood. This study analyzes the environmental impacts in the Western Department of Haiti on the suitability of agricultural land for the region’s main crops. To this end, relief, pedology, and climate were considered as relevant environmental factors for determining agricultural suitability, along with the physiological characteristics of plants. Therefore, for this analysis, maps, graphs, and tables were created based on specialized scientific literature, relief data, pedology, and climate. The results show that agricultural production in the Western Department is still precarious due to unfavorable environmental conditions, resulting in a decrease in local food production for consumption. When considering the drought tolerance of certain crops, it is concluded that smaller-scale cultivation, with an emphasis on providing food for families and local commerce, is feasible for corn, beans, and cassava.